Analiza stylistyczno-porównawcza karpackich obiektów sakralnych ze szczególnym uwzględnieniem greckokatolickiej świątyni w Łosiu - Bernadetta Wójtowicz (Studia Ecologiae et Bioethicae)
The article contains a stylistic comparison of the analysis of religious objects and their description of the landscape of the Carpathian region.